(untitled) (Baltic Journal of Sport and Health Sciences, 2011)
Research background and hypothesis. Dance is presented as a context to study emergent and nonlinear behaviour. Manipulating the task constraints and the agent/environment and agent / agent interactions is used to enhance the divergent production of motor responses, which is studied using observational methodology. Research aim. Our aim was to test an observation instrument capable of detecting synchronisations and spontaneous interactions in a group of dancers. Research methods. Seven dancers improvised during four five-minute trials involving four different constraints (Free movement; Free movement, but previously they had spent one minute breathing at the same time; Only walking and moving one’s arms; Free movement, but if one dancer stops, they must all stop at the same time). The recording instrument was the MatchVision Studio Software, and the data were analysed using THEME v.5 software (Magnusson, 1996, 2000). Research results. The results, as reﬂ ected by the T-patterns detected (twenty in Trial 1, eleven in Trial 2, twenty-one in Trial 3 and eight in Trial 4) and the frequency of the recorded events, show the following with these dancers: (1) the observational instrument developed has enabled us to analyse synchronisation and interaction of dancers, as well as to detect repeated sequences of events; (2) the most frequent event is the interaction in pairs using physical contact; (3) very strong constraints limit the emergence of varied patterns; and (4) a previous synchronisation of breathing enhanced the group’s synchronisation and the use of physical contact between members while dancing. Discussion and conclusions. The observational instrument developed has enabled us to analyze the synchronization and interaction of dancers, as well as to detect repeated sequences of events. Keywords: observational methodology, synchronization, constraints, nonlinear behaviour.